2021
DOI: 10.1155/2021/1173324
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Kidney Cell Pyroptosis in Chronic Kidney Disease and the Effects of Traditional Chinese Medicine

Abstract: Chronic kidney disease (CKD) is a major public health issue that is highly prevalent worldwide. Pyroptosis is an important pathological mechanism underlying kidney cell damage in CKD and is associated with the classic caspase-1-mediated pathway and nonclassic caspase-4/5/11-mediated pathway. The NLRP3-caspase-1-GSDMD signaling pathway is the key mechanism of kidney cell pyroptosis in CKD, and noncoding RNAs such as lncRNAs and miRNAs are important regulators of kidney cell pyroptosis in CKD. In addition, the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Quercetin (C5H10O7; Figure 1), a flavonol widely present in nature in the form of glucosides (Ulusoy and Sanlier, 2020), is one of the main components of different TCM, including Radix Bupleuri, Mulberry leaves, Sophorae Fructus, Inulae Flos, and Crataegi Fructus (Ding et al, 2021a;Shi et al, 2021;Tu et al, 2022). Many studies have demonstrated that quercetin has a wide range of pharmacological effects such as anti-cancer, antibacterial, anti-oxidation, and memory impairment improvement (Horowitz and Zunszain, 2015;Suganthy et al, 2016;Babaei et al, 2018a;Kashyap et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (C5H10O7; Figure 1), a flavonol widely present in nature in the form of glucosides (Ulusoy and Sanlier, 2020), is one of the main components of different TCM, including Radix Bupleuri, Mulberry leaves, Sophorae Fructus, Inulae Flos, and Crataegi Fructus (Ding et al, 2021a;Shi et al, 2021;Tu et al, 2022). Many studies have demonstrated that quercetin has a wide range of pharmacological effects such as anti-cancer, antibacterial, anti-oxidation, and memory impairment improvement (Horowitz and Zunszain, 2015;Suganthy et al, 2016;Babaei et al, 2018a;Kashyap et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more effective NS treatment drugs and strategies still need to be further investigated. In recent years, TCMs are increasingly becoming the promising therapeutic drugs for kidney diseases for their low side effects and commendable pharmacological activities [ 33 ]. FHD is a classical TCMs firstly recorded in Synopsis of the Golden Chamber and widely used in the treatment of edema and dysuria [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen-associated molecular patterns(PAMPs) damage-associated molecular patterns (DAMPs), and altered homeostatic processes (HAMPs) stimulate the oligomerization and activation of PRRs, ASCs, and inflammatory caspases to assemble into inflammasomes [ 14 ]. Canonical inflammasomes assembled by NLRP1 [ 15 ], NLRP3 [ 16 ], NLRC4 [ 17 , 18 ], AIM2 [ 19 ], pyrin [ 20 , 21 ], and other proteins mediate the classical pyroptotic pathway. Other PRRs, including NLRP6 [ 22 ], NLRP7 [ 23 ], NLRP9b [ 24 ], NLRP12 [ 25 ], and IFI16 [ 26 ] can also assemble pro-pyroptotic inflammasomes.…”
Section: Pyroptosismentioning
confidence: 99%